Analysis of the venous thromboembolic risk associated with severe postpartum haemorrhage in the NOHA First cohort - Chauleur, Céline; Cochery-Nouvellon, Eva; Mercier, Eric; Aya, Guy; Marès, Pierre; Mismetti, Patrick; Lissalde-Lavigne, Géraldine; Gris, Jean-Christophe (Thrombosis and Haemostasis, 2008)
Severe postpartum haemorrhages (PPH) are responsible for maternal morbidity/mortality. Their complex management sometimes requires haemostatic supplementation, and therapeutic trials on fibrinogen or activated factor VII, which may add to the thrombotic risk, are currently being considered. Furthermore, there is a risk of venous thromboembolism (VTE) during the postpartum period, hence we studied the relationship between severe PPH and VTE in women during their first pregnancy. Among the 32,463 women enrolled between January 1, 1999 and February 1, 2004 in the NOHA First cohort, 317 developed severe PPH, 11 postpartum VTE and 60 had postpartum superficial vein thrombosis (SVT). In the women with severe PPH, whilst there were no episodes of VTE, there were three episodes of SVT, which occurred 6 weeks postpartum. All of the women with severe PPH received packed red blood cell (RBC) units, 29 (9.1%) platelets units, 51 (16.1%) fresh frozen plasma and 29 (9.1%) fibrinogen concentrates. Three patients with both severe PPH and SVT received only packed RBC. Severe PPH or packed RBC unit transfusion were associated with postpartum SVT (adjusted relative risk: 5.3 (1.6–17) and 4.7 (1.5–15) respectively), independent of caesarean section delivery and low-molecular- weight heparin (LMWH) use in the postpartum, but were not independent indicators of one another. This the VTE and SVT risks associated with severe PPH are low (<1% and <2%, respectively).Severe PPH increases the risk of postpartum SVT, but transfusion with platelet units and plasma supplementation using fresh frozen plasma or fibrinogen concentrates do not markedly modulate the risk of venous thrombosis.
Keywords: Postpartum haemorrhage; thrombosis; deep vein thrombosis; superficial vein thrombosis